IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) DALAM MEMBENTUK KARAKTER SISWA DI UPTD SMP NEGERI 2 SENGKANG KABUPATEN WAJO - Sumarni; Besse Sulfiani; Angga Alhamdani; Panessai Sir; Muhammad Asrul Monang; Alifa Arwindi Adiamin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the importance of student character building as part of the national education goals. The Pancasila Student Profile Strengthening Project (P5) is a program integrated into the Merdeka Curriculum to develop students' character values in accordance with the six main dimensions of the Pancasila Student Profile. This research uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The subjects of this study were the principal, deputy principal for curriculum, and teachers at UPTD SMP Negeri 2 Sengkang. The results showed that the implementation of P5 was carried out through three main stages, namely planning, implementation, and evaluation. In the implementation process, the school has formed an implementation team, compiled project modules, and determined dimensions and themes according to student needs. Evaluation is carried out periodically through assessment and reflection. Based on these results, it can be concluded that the implementation of Projek P5 at UPTD SMP Negeri 2 Sengkang has been running well and contributes to shaping student character according to the values of Pancasila.